2013
DOI: 10.1007/s00418-013-1113-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MAPK signal transduction proteins in an ischemia/reperfusion model of mouse intestine using in vivo cryotechnique

Abstract: Intestinal ischemia and ischemia-reperfusion rapidly progress to tissue destruction and reconstruction of functional organs. To date, precise immunolocalizations and the timing of appearance of cell signaling components under such conditions have not been well visualized. Mitogen-activated protein kinase (MAPK) signal transduction pathways have been reported to be activated under various types of cell damage, and cyclic AMP response element-binding protein (CREB) was directly phosphorylated with various cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The present application of IVCT to morphological analyses of skeletal muscle tissues has clearly demonstrated the congestion of erythrocytes usually flowing in blood vessels along with the decrease of sarcomere length of contracted muscle fibers. Such erythrocyte congestion has already been observed in other organs of living mice under abnormal conditions, where blood circulation was considered to be impaired, because of heart-arrest conditions [ 17 , 28 ], ischemic model by blood vessel ligation [ 3 ] or thrombus formation by tumor cell metastasis [ 26 ]. It has been suggested that the blood flow into contracting muscle tissues is usually perturbed upon intensive muscle contraction, presumably due to the temporarily increased intramuscular pressure [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present application of IVCT to morphological analyses of skeletal muscle tissues has clearly demonstrated the congestion of erythrocytes usually flowing in blood vessels along with the decrease of sarcomere length of contracted muscle fibers. Such erythrocyte congestion has already been observed in other organs of living mice under abnormal conditions, where blood circulation was considered to be impaired, because of heart-arrest conditions [ 17 , 28 ], ischemic model by blood vessel ligation [ 3 ] or thrombus formation by tumor cell metastasis [ 26 ]. It has been suggested that the blood flow into contracting muscle tissues is usually perturbed upon intensive muscle contraction, presumably due to the temporarily increased intramuscular pressure [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia/reperfusion damage also occurs in other tissues, such as intestine. Chen et al (2013) have used their well-documented in vivo cryotechnique (IvCT), known to preserve soluble cellular components (such as signal transduction molecules) to investigate the involvement of the eRK1/2 signal transduction pathway after mouse intestinal ischemia/reperfusion by immunostaining for peRK1/2 and pCReB on frozen, freeze-substituted tissue sections. In control tissue sections, eRK immunoreactivity was widely observed in the cytoplasm of intestinal epithelial cells, whereas peRK1/2 was much more restricted in distribution to some epithelial cells present in the crypt region and at the tops of villi.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%